The Effect of Psychological Support Training Program on Self-Efficacy and Goal-Orientation among a Group of Syrian Refugee Female Trainees - Aburayash, Hussen (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to study the effect of a training program of psychological support on self-efficacy and goal-orientation among a group of Syrian trainees. The study sample consisted of (44) participants who were chosen intentionally. The sample was distributed into two groups: experimental and control, with 22 students in each group. Methods: To achieve the aim of the study, a quasi-experimental method was used. Two tools were applied: perceived self-efficacy and goal-orientation. The training program built by the researcher was applied to the experimental group. Results: The results showed that there were statistically significant differences between the average responses of the experimental and control groups in the post-measurement, in favor of the experimental group to which the training program was applied. Conclusion: The study recommends building and implementing training programs for psychological support for the youth.